“Beyond laughter”: a systematic review to understand how interventions utilise comedy for individuals experiencing mental health problems - Kafle, Eshika; Papastavrou Brooks, Cat; Chawner, Dave; Foye, Una; Declercq, Dieter; Brooks, Helen (Frontiers in Psychology, 2023)
Introduction There is evidence for the impact of comedy and humour for mental health and wellbeing. Existing systematic reviews have concluded laughter has a positive impact on wellbeing, however other potential benefits of comedy interventions have remained under explored. The aim of the current study was to synthesise current evidence for comedy/humour interventions and evaluate mechanisms through which comedy interventions may impact upon the recovery of those experiencing psychological distress, using the Connectedness, Hope, Identity, Meaning and Purpose and Empowerment (CHIME) framework. Methods Five electronic databases were searched for studies exploring the impact of interventions using comedy on wellbeing and mental health recovery, from earliest record until January 2023. Grey literature was obtained via contacting experts in comedy interventions for mental health and supplemented by an internet search for comedy interventions. To be eligible for inclusion, studies had to include primary data, published in English or German, and explore a population of adults, with self-reported distress or a self-reported/diagnosed mental health condition. Studies included only explored interventions which utilised comedy as the main intervention and aimed to induce ‘simulated’ laughter, in response to a stimulus. 17 studies were included in the review. Results Studies were found to have positive impact on mental health symptoms and several mechanisms of the CHIME framework for recovery, including connectedness, hope, identity and empowerment. Potential theorised mechanisms for change included confidence in new skills, promotion of social skills, opportunities for social interaction, laughter, vulnerability, and cognitive flexibility. The current review found that comedy/humour interventions are beneficial for mental health recovery and wellbeing and found preliminary evidence for a range of mechanisms through which comedy may have positive impact. Discussion Further research should focus on qualitative exploration of the mechanisms by which comedy interventions may have impact on wellbeing and mental health recovery for specific populations and within different settings. It is concluded that there is a need for transdisciplinary collaboration in research on comedy interventions, which brings together the expertise of comedians delivering/developing interventions, those with lived experience of mental health issues and researchers from both health sciences and humanities disciplines.